The Primary Care Clinic as Writing Space. (July 2019) - Opel, Dawn S.; Hart-Davidson, William
In a primary care health clinic, providers before, after, and throughout their shifts retrieve archival patient information and document new empirical data from each patient encounter into an electronic medical record (EMR). This documentation, called charting, contributes to ever increasing workload and provider burnout. While a provider may not perceive it to be, "charting" is writing work, and the clinic is a writing space. In this article, we use the concept of writing stewardship to examine a needs analysis of workflow in a family health center. We argue that the addition of writing stewards would shift the burden of documentation practices to distribute writing throughout the clinic, not primarily on providers. The implications of this are twofold: first, that writing studies researchers can help clinics write more efficiently and, second, that patient outcomes improve as a result of improved clinical communication.